חלומות שווא בהגותו של מנחם שלם - וישי, תאמז' (מחשבת ישראל, 2023)
Menahem Shalem (Prague/Central Europe, ca. 1350 – ca. 1420) formulated theoretical positions about dreams and imaginations on the basis of Maimonides and Narboni, which can be read against the background of the Hussite revolution as a critique of religious phantasmagorias and fanaticism. Shalem identified a mechanism of symbolic institution that takes place in dreams: the “prior opinions” (or prejudices) of human beings leave traces in their imaginative faculties; these traces impact the dreams they have, and the dreams lend a semblance of objective reality or truth to their prior opinions. As a consequence, their prior opinions are engraved in the mind and become firm convictions that cannot be refuted by rational arguments.